Perspectives on enhancing physical activity and diet for health promotion among at-risk urban UK South Asian communities: a qualitative study - Cross-Bardell, Laura; George, Tracey; Bhoday, Mandeep; Tuomainen, Helena; Qureshi, Nadeem; Kai, Joe (BMJ Publishing Group, 2015)
Objectives